Antibacterial and Antioxidant Activity of the Fruit of Macaranga tanarius, the Plant Origin of Taiwanese Green Propolis - Yi-Hsuan Chien; Yu-Hsiang Yu; Siou-Ru Ye; Yue-Wen Chen (MDPI AG, 2022)
Taiwanese green propolis (TGP) is widely used in traditional medicine and exerts a broad spectrum of biological activities, including those anti-inflammatory and anti-cancer in nature, resulting from an abundant level of functional propolins (prenylated flavanone) in the TGP. However, the plant origin of TGP has not been clarified. In this study, we collected the surface material of Macaranga tanarius fruit and comparatively analyzed the chemical composition, antibacterial activity, and antioxidant activity with TGP. The results revealed that there was no difference between the chemical composition of the glandular trichome extract of M. tanarius and those in propolis. Moreover, M. tanarius fruit extract was enriched in propolins (C, D, F, and G) and effectively inhibited the growth of Gram-positive strains. Propolins, TGP, and M. tanarius fruit extract showed powerful free radical-scavenging and ferrous-reducing activity. Collectively, we have confirmed the plant source of TGP is M. tanarius, and this plant has the enormous potential to be developed as a pharmaceutical plant due to the potent biological activities and the high amount of functional propolins.